PATTERN AND FREQUENCY OF BLOOD TRANSFUSION REACTIONS: A THREE-YEAR RETROSPECTIVE STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Transfusion of blood is an important intervention that is regularly carried out in tertiary hospitals. It involves several potential adverse reactions varying from mild allergic reactions to potentially fatal complications. Hence, continuous monitoring and analyzing of these transfusion reactions are crucial to guarantee patient safety and optimize transfusion practices. Recognizing the pattern and occurrence of these transfusion reactions in a tertiary hospital setting is crucial to enhance haemovigilance programs. Consequently, the aim of this study was to identify the pattern and occurrence of transfusion reactions in our GEMS Hospital's in-patients, as documented in our hospital's blood center. Materials & Methods: This study utilized retrospective observational designs conducted in GEMS Hospital, a tertiary hospital, between January 2023 and December 2025. During the study duration, all transfusion reactions reported to our blood center due to blood and blood products transfusion were identified and analyzed using the institution's standard operation procedure. Results: Throughout the study duration, a total of 27,319 units of blood and blood components were distributed. There was a total of 78 transfusion reactions, which resulted in an overall rate of 0.29%. The most prevalent transfusion reaction was Febrile Non-Haemolytic Transfusion Reaction, which totaled 37 (47.4%). Allergic reactions accounted for 31 (39.7%), while other reactions were 10 (12.8%). Conclusion: In this study, the incidence of transfusion reactions was relatively low (0.29%) with the most common transfusion reaction being Febrile Non-Haemolytic Transfusion Reaction followed by allergic reactions.